(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2013)
This paper intends to explore the spatial concept of Chinese Architecture in Surabaya which was built prior 1945. The arrival of Chinese people decades ago brought along diverse culture that permeates the local Indonesian culture and once the Chinese settled down, the on-going cultural dialogue started to influence the Chinese in return. Most importantly, this cultural exchange process allowed the Chinese to introduce their own spatial architectural concept, which seems prescriptive, that applied to all buildings typology, starting from house, temple and the palace. In Surabaya context, the Chinese fixed-prescriptive spatial architectural concept observed to deviate from norm. Hence, this paper intends to explore this phenomenon comparing Surabaya’s Chinese spatial architectural concept, represented by temples, prayer houses as well as houses built prior 1945 era, to the Chinese original spatial concept. This research hopes to conclude that the main difference between the two is the absence of light well which known as Tien Ching which was originally located in the middle of the building in all Chinese Architecture in Surabaya.